Usulan Perbaikan Penempatan Barang pada Area Pemeriksaan Inbound Gudang Logistik dengan Metode Class Based Storage - Yevita Nursyanti; Habib Rais (Politeknik ATI Padang, 2021)
The company runs a business by providing services related to storage and handling of goods in warehouses to its customers, namely PT Semarang Autocom Manufacturing Indonesia Jepara (SAMI-JF) and Tugu (SAMI-TF). Goods from SAMI-JF and SAMI-TF customers have similarities so that checkers often have difficulty identifying and finding items to be inspected. This causes delays in checking goods in the inbound inspection area, resulting in a delay in the putaway process. This study aims to provide suggestions for improving the placement of goods in the inbound inspection area in the logistics warehouse. The method used is the Class Based Storage method. Based on data processing, the results of the proposed improvements are the location of goods placement in the logistics warehouse divided into two groups, namely groups A and B. Goods from SAMI-JF customers use the area from block 1 to block 19, while goods from SAMI-TF customers use blocks 20 to 38 blocks with a total distance of 2593.5 m. The results of the proposal are expected to reduce the occurrence of delays in checking goods in the inbound inspection area and completing put aways.